(untitled) (Research, Society and Development, 2019)
This report comes from a review of the academic dissertation, “A study of the incorporation of original texts to the mathematics education: seeking joint criteria between history and teaching", presented at Programa de Pós-Graduação em Teaching science and Math of the Federal Institute of education, science and technology of the State of Ceará (IFCE). The theme emerges about the importance of investigating the use of an original document for teaching mathematics, the Rhind Papyrus, developing activities to be applied in high school. The research was qualitative, methodological approach, and a bibliographical study of documents from data collection. One of the contributions arising from the process, the criteria used to enter the history of mathematics in the context of the classroom. As a conclusion we observed the need of knowledge of historiographical perspective and about the criteria for treating an original document for teaching. And from the results, emphasized the importance of vocational training on the subject.